Effects of inclination angle on mixed convective nanofluid flow in a double lid-driven cavity with discrete heat sources. (March 2017) - Hussain, S.; Ahmad, S.; Mehmood, K.; Sagheer, M.
Highlights: Augmentation in ϕ and Ri causes a significant increase in the heat transfer. Increase in γ reduces SHT, SFF, average temperature and kinetic energy. Increase in Ri causes an enhancement in entropy generation and kinetic energy. Increase in γ causes to increase Nuavg due to S1 and decrease in Nuavg due to S2. Abstract: In the present study, numerical simulations are performed to examine the effect of inclination angle on the heat transfer of Al2 O3 –water nanofluid for mixed convection flows in a partially heated double lid driven inclined cavity. At the lower wall of the cavity, two heat sources are fixed with the condition that the remaining part of the bottom wall is kept insulated. Top wall and vertically moving walls are maintained at constant cold temperature. Buoyant force is responsible for the flow along with two moving vertical walls. The governing equations are discretized with the help of finite element method in space and the Crank–Nicolson in time. For the spatial discretization, nonconforming Stokes element Q ∼ 1 / Q 0 of 2nd order accuracy for velocity, temperature and 1st order accuracy for pressure is utilized. The discretized nonlinear systems of equations are treated by using the Newton method and the associated linear subproblems are solved using Gaussian elimination method in each time level. Numerical results are presented and analyzed by means of streamlines, isotherms, tables and some useful plots. Impact of emerging parameters on the flow, in specific ranges such as Reynolds number ( 1 ⩽ Re ⩽ 100 ), Richardson number ( 0.01 ⩽ Ri ⩽ 10 ), nanoparticle volume fraction ( 0 ⩽ ϕ ⩽ 0.04 ) as well as inclination angle of cavity ( 0 ° ⩽ γ ⩽ 45 ° ) are investigated and findings are exactly of the same order as that of the previously performed analysis in the literature. Calculations of average Nusselt number, average temperature, average entropy generation due to heat transfer and fluid friction and kinetic energy are the main focus of our study.